2011
DOI: 10.1027/2151-2604/a000043
|View full text |Cite
|
Sign up to set email alerts
|

Digit Repetition Effect in Two-Digit Number Comparison

Abstract: Previous data from two-digit number naming show that when target and prime numbers share one digit at different positions (e.g., target 28 and prime 86 or 72) an inhibition effect may be observed (Ratinckx, Brysbaert, & Fias, 2005). Such an effect has been ascribed to the mechanism of morpho-phonological transcoding from Arabic to verbal format. We evaluate the alternative hypothesis of an inhibition effect arising during the Arabic form processing when two different syntactic values have to be assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For instance, it is not restricted to magnitude comparison. Multi-digit number processing is a task-overlapping research topic and can include parity processing (Reynvoet et al, 2011), number matching (Fischer & Campens, 2009; García-Orza & Damas, 2011; Zhou et al., 2008), or number naming (Brysbaert, 1995; Brysbaert, Fias, & Noël, 1998; Gazzellini & Laudanna, 2011; Ratinckx, Brysbaert, & Fias, 2005), but also more complex cognitive demands such as addition (Klein et al, 2010; Moeller, Klein, et al, in press), subtraction (Kong et al, 2005; Lindemann & Tira, 2011), or multiplication (Domahs, Delazer, & Nuerk, 2006; Domahs et al, 2007).…”
Section: Indexing Multi-digit Number Integration: Definition and Elab...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it is not restricted to magnitude comparison. Multi-digit number processing is a task-overlapping research topic and can include parity processing (Reynvoet et al, 2011), number matching (Fischer & Campens, 2009; García-Orza & Damas, 2011; Zhou et al., 2008), or number naming (Brysbaert, 1995; Brysbaert, Fias, & Noël, 1998; Gazzellini & Laudanna, 2011; Ratinckx, Brysbaert, & Fias, 2005), but also more complex cognitive demands such as addition (Klein et al, 2010; Moeller, Klein, et al, in press), subtraction (Kong et al, 2005; Lindemann & Tira, 2011), or multiplication (Domahs, Delazer, & Nuerk, 2006; Domahs et al, 2007).…”
Section: Indexing Multi-digit Number Integration: Definition and Elab...mentioning
confidence: 99%
“…A number pair is termed unit-decade compatible whenever separate decade and unit digit comparisons lead to the same decision (as for the pair 42_57, 4 < 5 and 2 < 7) and incompatible when unit and decade comparisons lead to different decisions (47_62; 4 < 6, but 7 > 2). Since its discovery by Nuerk et al (2001), several studies in children and adults have shown that incompatible number pairs are processed slower and with more errors than compatible pairs (Ganor-Stern, Pinhas, & Tzelgov, 2009; Ganor-Stern & Tzelgov, 2011; Ganor-Stern, Tzelgov, & Ellenbogen, 2007; Gazzelini & Laudanna, 2011; Knops, Nuerk, Sparing, Foltys, & Willmes, 2006; Korvorst & Damian, 2008; Landerl & Kölle, 2009; Macizo & Herrera, 2008, 2010; Macizo, Herrera, Paolieri, & Román, 2010; Mann et al, 2011; Moeller, Fischer, Nuerk, & Willmes, 2009; Moeller, Nuerk, et al, 2009; Nuerk, Weger, & Willmes, 2002, 2004, 2005Pixner, Moeller, Zuber, & Nuerk, 2009; Ratinckx et al, 2006; Wood, Nuerk, Freitas, et al, 2006; Wood, Nuerk, & Willmes, 2006). The existence of the UDCE is strong evidence against a purely holistic magnitude processing of multi-digit numbers because overall distance is matched between compatible and incompatible number pairs.…”
Section: Specific Multi-digit Number Processing Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Gazzellini and Laudanna (2011) examine the digit repetition effect in two-digit number comparison in a priming study and show that this effect is not only due to asemantic morphophonological transcoding but seems to rely on Arabic-syntactic processing with decomposed processing of tens and units.…”
mentioning
confidence: 99%
“…So far, the compatibility effect has been observed in several studies (e.g., Ganor-Stern & Tzelgov, 2011;Gazzellini & Laudanna, 2011;Moeller, Fischer, Nuerk, & Willmes, 2009;Nuerk, Moeller, Klein, Willmes, & Fischer, 2011;Nuerk & Willmes, 2005). Yet, the mode of compositional processing of two-digit numbers can be either parallel or sequential (e.g., Meyerhoff et al, 2012;Zhang & Wang, 1995).…”
Section: Introductionmentioning
confidence: 91%